Problems of documenting the accounting of intangible assets - V.V. Yasyshena (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The situation related to the primary documents and the structure of their forms for accounting for intangible assets needs to be resolved. The existence of a number of options for the use of forms of primary documents for accounting for intangible assets, which complicates the documentation process, as the primary forms are partially collected and regulated by several laws and regulations. The need to streamline and summarize the primary documents for accounting for intangible assets and goodwill is emphasized, the order of which should be regulated by a single document. It is recommended to implement the Guidelines for the use of forms of primary accounting of intangible assets and goodwill, with a set of relevant details, which should include documents that will reflect all groups of intangible assets, not just those related to intellectual property. Emphasis was placed on the need to develop primary documentation that will reflect the operations with the formation of intangible assets that will create internal goodwill. It is noted that the use of uniform, agreed forms of primary accounting of intangible assets is also necessary to improve the quality of inspections by regulatory authorities. Primary accounting forms for inventory of intangible assets № IA-4 «Inventory description of intellectual property rights (PR)» and № IA-5 «Inventory description of objects of the right to use natural resources, property and other intangible assets» are developed and recommended to use. It is substantiated to make clarifications and introduce additional details to the inventory descriptions, which is necessary to improve the quality of information formation during the inventory. Emphasis is placed on the need to disclose in the process of inventory objective information about intellectual property objects by checking them for functional compliance, to record the working condition of such objects.